How Robust Are the Surface Temperature Fingerprints of the Atlantic Overturning Meridional Circulation on Monthly Time Scales?. Issue 8 (20th April 2018) - Alexander‐Turner, R.; Ortega, P.; Robson, J. I.
Abstract: It has been suggested that changes in the Atlantic Meridional Overturning Circulation (AMOC) can drive sea surface temperature (SST) on monthly time scales (Duchez et al., 2016, https://doi.org/10.1007/s00382‐015‐2918‐1 ). However, with only 11 years of continuous observations, the validity of this result over longer, or different, time periods is uncertain. In this study, we use a 120 yearlong control simulation from a high‐resolution climate model to test the robustness of the AMOC fingerprints. The model reproduces the observed AMOC seasonal cycle and its variability, and the observed 5‐month lagged AMOC‐SST fingerprints derived from 11 years of data. However, the AMOC‐SST fingerprints are very sensitive to the particular time period considered. In particular, both the Florida current and the upper mid‐ocean transport produce highly inconsistent fingerprints when using time periods shorter than 30 years. Therefore, several decades of RAPID observations will be necessary to determine the real impact of the AMOC on SSTs at monthly time scales. Plain Language Summary: The Atlantic Meridional Overturning Circulation (AMOC) is thought to be a key element of the Earth's climate as it plays an important role in redistributing heat from the Equator toward the North Atlantic and the Arctic. Therefore, understanding how variations in the AMOC affect the wider climate is an important question for climate prediction. Unfortunately, the AMOC is difficult to measure, and it has only been continuously measured since 2004 at the latitude of 26°N. A recent paper (Duchez et al., 2016, https://doi.org/10.1002/2017GB005667 ) suggests that these observations can be exploited to predict the surface temperature of the ocean in the North Atlantic region up to 5 months ahead. However, given the short observational period (only 13 years so far), our study questions if this link is sufficiently robust. By combining the use of longer observational records, and a 120 yearlong simulation of the climate, we show that the link between the AMOC and surface temperatures is highly sensitive to the time epoch considered. Therefore, we advocate the need of continuing the current observational efforts for at least two more decades to robustly determine the AMOC potential for predicting the Atlantic several months ahead. Key Points: The impact of Florida Strait and Ekman transports on surface temperatures from monthly observations depends on the chosen period Our model suggests that 30 to 50 years of observations will be needed to robustly constrain the AMOC fingerprints on monthly time scales Part of the uncertainty in the simulated fingerprints is linked to stochastic variability in the atmospheric heat fluxes